Ambient microdroplet annealing of nanoparticles. Issue 18 (8th April 2021) - Ray Chowdhuri, Angshuman; Spoorthi, B. K.; Mondal, Biswajit; Bose, Paulami; Bose, Sandeep; Pradeep, Thalappil
Abstract : Polydisperse silver nanoparticles were converted to a highly ordered assembly of nanoparticles by microdroplet-induced chemistry, under ambient conditions, within seconds. Abstract : Conversion of polydisperse nanoparticles to their monodisperse analogues and formation of organized superstructures using them involve post synthetic modifications, and the process is generally slow. We show that ambient electrospray of preformed polydisperse nanoparticles makes them monodisperse and the product nanoparticles self-assemble spontaneously to form organized films, all within seconds. This phenomenon has been demonstrated with thiol-protected polydisperse silver nanoparticles of 15 ± 10 nm diameter. Uniform silver nanoparticles of 4.0 ± 0.5 nm diameter were formed after microdroplet spray, and this occurred without added chemicals, templates, and temperature, and within the time needed for electrospray, which was of the order of seconds. Well organized nanoparticle assemblies were obtained from such uniform particles. A home-made and simple nanoelectrospray set-up produced charged microdroplets for the generation of such nanostructures, forming cm 2 areas of uniform nanoparticles. A free-standing thin film of monodisperse silver nanoparticles was also made on a liquid surface by controlling the electrospray conditions. This unique method may be extended for the creation of advanced materials of many kinds.